2010
DOI: 10.1021/jp102024y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Thermodynamic Study of Three Monofluoronitrobenzene Isomers

Abstract: The present work reports the thermodynamic study performed on three monofluorinated nitrobenzene derivatives by a combination of experimental techniques and computational approaches. The standard (p degrees = 0.1 MPa) molar enthalpies of formation in the liquid phase of the three isomers of fluoronitrobenzene were derived from the standard molar energies of combustion, in oxygen, at T = 298.15 K, measured by rotating bomb combustion calorimetry. The vapor pressure study of the referred compounds was done by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…32 In previous studies made in our research group, it was established that the correction of +4 kJ · mol -1 suggested by Cox is not sufficient to account for the destabilization effects observed as a result of the steric interaction between a halogen atom and the nitro group as ortho substituents in a benzene ring and that a larger enthalpic correction is needed. Ribeiro da Silva et al 25 suggested an additional correction term of ∼+22 kJ · mol -1 in this case, in addition to the +4 kJ · mol -1 correction recommended by Cox.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…32 In previous studies made in our research group, it was established that the correction of +4 kJ · mol -1 suggested by Cox is not sufficient to account for the destabilization effects observed as a result of the steric interaction between a halogen atom and the nitro group as ortho substituents in a benzene ring and that a larger enthalpic correction is needed. Ribeiro da Silva et al 25 suggested an additional correction term of ∼+22 kJ · mol -1 in this case, in addition to the +4 kJ · mol -1 correction recommended by Cox.…”
Section: Resultsmentioning
confidence: 94%
“…Using the methodology developed by Cox, it was possible to estimate ∆ f H m°( g) for the difluoronitrobenzene isomers according to the four different approaches, presented in Figure 6, taking into account the following literature values of the gasphase standard molar enthalpies of formation: ∆ f H m°( benzene,g) )(82.6 ( 0.7)kJ · mol -1 , 66 ∆ f H m°( fluorobenzene,g))-(115.9 ( 1.4) kJ · mol -1 , 66 ∆ f H m°( nitrobenzene,g) ) (67.5 ( 0.5) kJ · mol -1 , 66 ∆ f H m°( o-difluorobenzene,g) ) -(293.7 ( 0.9) kJ · mol -1 , 66 32 and ∆ f H m°( p-fluoronitrobenzene,g) ) -(133.9 ( 1.4) kJ · mol -1 . 32 In previous studies made in our research group, it was established that the correction of +4 kJ · mol -1 suggested by Cox is not sufficient to account for the destabilization effects observed as a result of the steric interaction between a halogen atom and the nitro group as ortho substituents in a benzene ring and that a larger enthalpic correction is needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correction term of 4 kJ Á mol À1 suggested by Cox [37] due to steric destabilization, whenever two substituents are attached in adjacent carbon atoms of the ring, need to be further evaluated, since a few cases are already known in the literature in which it is necessary to include a higher value of enthalpic correction of destabilization. In particular, Ribeiro da Silva et al [4,[40][41][42][43][44] found that a large additional correction is necessary to account for the interaction between a halogen atom and the nitro group as a ortho pair of substituents in a benzenic ring.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of nitrobenzene derivatives have been studied in our Research Group [17][18][19][20][21][22][23][24][25][26][27][28][29]. Recently we turned our attention on acetophenone derivatives having already studied some monoand dichloroacetophenone isomers [30,31].…”
Section: Introductionmentioning
confidence: 99%